Z wie Zacharias - O'Brien, Robert C. (Benziger, 1977)
Ann Burden believes, after living alone for a year, that she is the only survivor of a nuclear war which has destroyed most the world. However, she encounters John Loomis. As time wears on, Loomis becomes too domineering and she is faced with a new challenge in survival.
EST: Z for Zachariah (dt.)
Keywords: War stories, American -- Juvenile fiction; Tagebuch